Chemistry made easy a compilation of reviewers in Chem 14. (Manila : Learning Resource Center, University of the Philippines Manila, [2008].)
This instructional material was designed to give first year students of UP Manila a preview of what to expect during departmental exams in General Chemistry I (Chem 14). The questions and topics are based on the syllabus and are intended to offer practice exercises and enhance the competency of the students.
Cover title: Chemistry made easy : a compilation of reviewers in Chem 14.
UCASM-2316 (UCASM002316)
Keywords: Chemistry